Central venous catheter insertion in adult patients: a best practice implementation project. Issue 3 (5th September 2021) - Ferreira, Juliana D.N.; dos Santos, Kelli B.; Siqueira, Eduardo C.; Gomes, Edimar P.; Martini, Larissa; Fraga, João B.P.; Lima, Maria Augusta M.; Poveda, Vanessa B.
ABSTRACT: Introduction and aims: The central venous catheter (CVC) is an indispensable device in the daily practice of modern medicine. Thus, the implementation of CVC interferes with the care of a large number of patients. This project aimed to implement the best practices in the insertion of CVC in adult hospitals in Brazil. Methods: The project had three phases, including forming a team and conducting the baseline audit; identifying problems and developing strategies; and conducting a follow-up audit to assess the impact on compliance with best practices. A baseline audit was conducted at a public Hospital in Minas Gerais, Brazil, in June and July 2019. For data collection, direct observation of the procedure was performed and through the PACES (Practical Application of Clinical Evidence System) audit and feedback tool to check the compliance criteria established in the literature. After implementation, a second audit was conducted in August 2019. Results: During the baseline audit, the absence of adequate compliance with the criteria for using an ultrasound to insert the catheter and correct hand hygiene before the procedure was identified. Theoretical–practical training was carried out, including the use of ultrasound to perform the procedure, using an adapted mannequin. The follow-up audit showed an improvement in the compliance rate for the following audit criteria: physical assessment before the procedure (92–100%); evaluation of the most suitable vein for insertion of the catheter, avoiding the femoral vein (92–100%); correct hand hygiene before the procedure (58–100%); maintenance of asepsis throughout the procedure (83–91%) and use of ultrasound to guide venous catheterization (17–100%). Conclusion: The current project proved that training the team can be effective in optimizing the implementation of evidence.